Queenship and the Women of Westeros: Female Agency and Advice in Game of Thrones and A Song of Ice and Fire Zita Eva Rohr and Lisa Benz (eds.) Cham: Palgrave Macmillan, 2020. Issue 2 (2022) - Storey, Gabrielle
No abstract available